SEPTIC ABORTION MORTALITY IN HOSPITAL CAYETANO HEREDIA - Maradiegue Méndez, Eduardo (2015)
A retrospective study of 34 maternal deaths per septic abortion occurred in the Cayetano Heredia Hospital in Lima, Peru, during the period from 1975 to 1984, with a mortality rate of septic abortion from 71.74 deaths per ten thousand abortions. Mortality from septic abortion during the period was 35.79% of the total maternal mortality. The average age of patients was 27.2 years with rank between 14 and 43 years; The 17.64% were younger than 20 years. The average three living children, ranging between 0 and 13 children. 50% had stable family unit and total primigravid patients Erna married. The 52.94% (18/34) were from outside the area of influence of the hospital. 38.2% (13/34) of septic abortion remained dead for less than 24 hours.